System-wide learning from root cause analysis: a report from the New South Wales Root Cause Analysis Review Committee. Issue 6 (29th July 2010) - Taitz, Jonny; Genn, Kelvin; Brooks, Vanessa; Ross, Deborah; Ryan, Kathleen; Shumack, Bronwyn; Burrell, Tony; Kennedy, Peter
Abstract : Background: Preventable errors are common in healthcare. Over the last decade, Root Cause Analysis (RCA) has become a key tool for healthcare services to investigate adverse events and try to prevent them from happening again. The purpose of this paper is to highlight the work of the New South Wales (NSW) RCA Review Committee. The benefits of correctly classifying, aggregating and disseminating RCA data to clinicians will be discussed. In NSW, we perform an average of 500 RCAs per year. It is estimated that each RCA takes between 20 and 90 h to perform. In 2007, the NSW Clinical Excellence Commission (CEC) and the Quality and Safety Branch at the Department of Health constituted an RCA review committee. 445 RCAs were reviewed by the committee in 14 months. 41 RCAs were related to errors in managing acute coronary syndrome. Results and discussion: The large number of RCAs has enabled the committee to identify emerging themes and to aggregate the information about underlying human (staff), patient and system factors. The committee has developed a taxonomy based on previous work done within health and aviation and assesses each RCA against this set of criteria. The effectiveness of recommendations made by RCA teams requires further review. There has been conjecture that staff do not feel empowered to articulate root causes which are beyond the capacity of the local service to address. Conclusion: Given the number of hours per RCA, it seems a shame that the final output of the process may not in fact achieve the desired patient safety improvements.